2020
DOI: 10.1007/s13399-020-00856-1
|View full text |Cite
|
Sign up to set email alerts
|

Single-step extraction–esterification process to produce biodiesel from palm oil mill effluent (POME) using microwave heating: a circular economy approach to making use of a difficult waste product

Abstract: This investigation explores single-step biodiesel synthesis using palm oil mill effluent (POME) as a feedstock. Normally considered a waste product from the extraction process of palm oil, POME treatment is difficult and can cause significant environmental pollution if discharged directly into watercourses. Fatty acids (FAs) present in POME were extracted and subsequently esterified in situ to FA methyl esters (FAME) suitable for use as biodiesel. The process of simultaneous extraction and esterification was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…This work is based upon our prior experimental work (Davies et al, 2020). A block flow diagram (Figure 1) was produced to show the key unit operations and major process streams to aid in simulation development.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This work is based upon our prior experimental work (Davies et al, 2020). A block flow diagram (Figure 1) was produced to show the key unit operations and major process streams to aid in simulation development.…”
Section: Methodsmentioning
confidence: 99%
“…We recently introduced the new experimental laboratory work focused on the recovery, extraction and esterification of the POME process to produce biodiesel (Davies et al, 2020;Balan et al, 2021;Semilin et al, 2021). The purpose of this article is to develop and optimise a "green" process for biodiesel production, based on our recent experimental work (Davies et al 2020;Balan et al, 2021;Semilin et al, 2021). The novel practical work focused on refining the single-step extraction-esterification process to produce biodiesel from POME using the MRT.…”
Section: Introductionmentioning
confidence: 99%
“…The achieved biodiesel yield was comparable with homogeneous catalysts. Davies et al [82] investigated the esterification of POME using H 2 SO 4 . A biodiesel yield of 89 % was attained under the optimized conditions of reaction time (15 min), catalyst loading (0.8 wt %), and reaction temperature (60°C).…”
Section: Homogeneous Acid-catalyzed Transesterificationmentioning
confidence: 99%
“…Therefore, microwave heating is faster than conventional heating, causing a higher biodiesel yield in minimum time. Davies et al [82] reported the single-step esterification-transesterification of POME for biodiesel production via microwave heating. The reaction conditions were kept at reaction temperatures of 100-150°C, catalyst loading of 0-1, and reaction time of 0-30 min.…”
Section: Microwave-assisted Transesterificationmentioning
confidence: 99%
“…Microwave-assisted chemistry is an environmentally friendly approach that can overcome limitations such as uneven heating, poor mixing, thermal stability of reagents, and high viscosity [6]. Such technology can be considered as a powerful, versatile, and flexible tool for chemical reactions, biomass treatment, and biocatalysis, which match with deep eutectic systems [7]. DESs were first proposed by Abbott et al as alternative solvents to ionic liquids (ILs) [8].…”
Section: Introductionmentioning
confidence: 99%